Pelatihan Pemanfaatan Kecerdasan Buatan Untuk Promosi Bagi Pelaku Usaha Kecil Menengah di Kota Palembang - Hartati, Eka; Aprizal, Yarza; Yuniansyah, Yuniansyah (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2024)
Training on the use of Artificial Intelligence used to create promotional media for Small and Medium Enterprises (SMEs) is one of the community service activities carried out by Lecturers at the Palcomtech Institute of Technology and Business. The aim of this activity is to increase the knowledge and abilities of SMEs assisted by PT. Pertamina International Unit III Plaju Refinery to create promotional media. The activities will be carried out on Sunday 17 December 2023 at the Pertamina Education Park which is located at Talang Putri, Plaju District, Palembang City. The training was attended by 33 business actors. The implementation method is carried out by means of presentations and practice using the Canva application which utilizes artificial intelligence to create promotional designs quickly and effectively. The implementation of this training activity went very well where all participants actively participated in the training and were able to create promotional designs for their respective businesses